Balancing home & career : skills for successful life management - Conrad, Pamela J. (Crisp Pub. Menlo ParkUS, 1995)
Provides help with exploring and defining home responsibility, career requirements, and how to spend leisure time. Offers options which can assist the reader to invest quality time in his/her various commitments, such family, career, hobbies etc.